Automobile heat insulation film and preparation method thereof
Through the combination of nano-oxides and modified materials and ultrasonic oscillation technology, the infrared and ultraviolet barrier rates and mechanical properties of automotive thermal insulation films are improved, and the problems of insufficient performance and poor weather resistance in the prior art are solved, thus achieving the problem of insufficient thermal insulation film performance and poor weather resistance in the existing technology. Higher insulation efficiency and longer service life.
Patent Information
- Application Number
- CN202411483747.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Existing automotive thermal insulation films are prone to aging under high temperature and strong light exposure, and their performance is degraded, and the ultraviolet absorber and light stabilizer fail over time, resulting in insufficient thermal insulation performance and weather resistance.
Using nano-indium tin oxide, nano-tungsten oxide, nano-titanium oxide, nano-zinc oxide and other nano-dispersion and modified materials, the ultrasonic oscillation technology is used to achieve uniform dispersion, and it is also combined with polymers such as polyethylene terephthalate. Mix to form a high-performance composite slurry, improving the tensile strength and optical properties of the thermal insulation film.
It significantly improves the infrared and ultraviolet barrier rate of the car's thermal insulation film, enhances mechanical properties and weather resistance, extends service life, and reduces the energy consumption of air conditioners in the car, protecting passengers and interior accessories from ultraviolet rays.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation films, and in particular to a thermal insulation film for an automobile and a preparation method thereof. Background Art
[0002] With the global climate change and the increasing awareness of environmental protection, the automotive industry has a growing demand for thermal insulation films. Automotive thermal insulation films can not only effectively block solar radiation and reduce the temperature inside the car, but also protect passengers from ultraviolet damage and extend the service life of materials inside the car. Therefore, the development of automotive thermal insulation films with excellent thermal insulation performance and durability has become an important issue in the industry.
[0003] Existing automotive thermal insulation films usually use traditional polymer materials, such as polyethylene terephthalate (PET) and polyurethane (PU). Although these materials can meet the thermal insulation requirements to a certain extent, their performance still has shortcomings. For example, the tensile strength of traditional polymers is low and they are easily aged under high temperature and strong light, resulting in the degradation of film performance. In addition, the ultraviolet absorbers and light stabilizers used in the prior art tend to lose their effectiveness over time, reducing the protective effect of the film.
[0004] Traditional automotive thermal insulation films still have deficiencies in terms of thermal insulation performance, mechanical strength and weather resistance. In particular, existing thermal insulation films are prone to aging under high temperature and strong light, resulting in performance degradation, and the UV absorbers and light stabilizers used gradually become ineffective over time, weakening the protection effect on passengers and objects in the car. In addition, the dispersion and compatibility issues of nanomaterials in polymer matrices in existing technologies are also a technical obstacle to improving the performance of thermal insulation films.
[0005] Chinese invention patent CN105348750A discloses a heat-insulating and UV-proof automobile film and a preparation method thereof, which uses polyethylene terephthalate, polytrimethylene terephthalate, polyimide, molybdenum disulfide, plasticizer, carboxymethyl cellulose, nano silicon dioxide, ethylene-α-olefin copolymer, antioxidant and anti-ultraviolet and anti-aging nanocomposite materials as raw materials. Compared with the prior art, since the nano zinc oxide composite material coated with nano cerium dioxide has the characteristics of resistance to ultraviolet radiation, heat resistance, non-toxicity, strong stability, etc., it can shield and reflect ultraviolet rays outside the film. Therefore, the preparation process of the heat-insulating and UV-proof automobile film is simple, and it has the characteristics of good heat insulation effect, high temperature resistance, UV resistance and aging resistance. The invention also provides a method for preparing an anti-ultraviolet and anti-aging nanocomposite material, and the anti-ultraviolet and anti-aging nanocomposite material has good anti-ultraviolet and aging resistance. However, it still needs to be improved in terms of heat insulation performance, mechanical strength and weather resistance. Summary of the invention
[0006] In view of the defects of the prior art, the present invention provides an automobile thermal insulation film prepared by using specific nano-oxides and modified materials. The thermal insulation film has high tensile strength, infrared and ultraviolet blocking rates, and aims to solve the problems of insufficient performance and poor weather resistance of the thermal insulation film in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A method for preparing an automobile thermal insulation film is as follows, in parts by weight:
[0009] Step 1, taking 0.4-0.6 parts of nano indium tin oxide powder, 0.05-0.2 parts of nano tungsten oxide powder, 0.05-0.2 parts of nano titanium oxide, 0.05-0.2 parts of nano zinc oxide powder and 0.05-0.2 parts of grinding aid, putting them into a ball mill for mixing and grinding; mixing the obtained mixed powder with 4-6 parts of water, and performing ultrasonic vibration to achieve dispersion, adding 0.02-0.04 parts of coupling agent and 1-1.5 parts of modified material to the dispersion, and stirring them fully to form a uniform composite slurry;
[0010] Step 2, weighing 1.4-1.8 parts of polyethylene terephthalate and 0.1-0.3 parts of plasticizer, dissolving them in 15-25 parts of ethyl acetate, adding 0.05-0.2 parts of dispersant, stirring to make it uniformly dispersed, adding 15-25 parts of water to the mixture, continuing to stir, and removing ethyl acetate through a distillation process, adding 0.01-0.015 parts of ethylene-vinyl acetate copolymer, 0.005-0.02 parts of ultraviolet absorber, 0.001-0.003 parts of light stabilizer 770, 0.004-0.06 parts of BYK-310 leveling agent, 0.0005-0.002 parts of silicone defoamer, mixing until a uniform state, to obtain a mixture; adding the composite slurry obtained in step 1 to the above mixture, stirring fully, and evaporating water to prepare a mixed slurry for coating;
[0011] Step 3: evenly apply the mixed slurry obtained in step 2 on the glass surface to obtain a coating, and place the coated glass in an oven for drying until the solvent in the slurry is completely volatilized to obtain a car thermal insulation film.
[0012] The grinding aid is sodium citrate.
[0013] The ultrasonic oscillation time is 40 to 60 minutes, the ultrasonic power is 200 to 400 W, and the ultrasonic frequency is 20 to 60 kHz.
[0014] The coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.
[0015] The plasticizer is polyisobutylene.
[0016] The dispersant is polyvinyl pyrrolidone.
[0017] The evaporated water is such that the solid content reaches 70-80%.
[0018] The wet film thickness of the coating is controlled at 0.15 to 0.25 mm.
[0019] The preparation method of the modified material is as follows, in parts by weight:
[0020] S1. Weigh 0.01-0.03 parts of dibenzoyl peroxide, mix it with 4-6 parts of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0021] S2, weigh 5 to 10 parts of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 8 to 10 parts of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, add them to 25 to 35 parts of ethyl acetate, heat to 60 to 80° C. and keep for 10 to 20 minutes, dropwise add the initiator solution of step S1, raise the temperature to 90 to 110° C., keep for 1 to 2 hours, and obtain a pretreated product;
[0022] S3, mixing the pretreated material obtained in step S2, 30 to 50 parts of polyurethane resin, and 0.05 to 0.1 parts of hexamethylene diisocyanate, heating to 50 to 70° C., and maintaining for 40 to 60 minutes to obtain a modified material.
[0023] In the method for preparing the automotive thermal insulation film of the present invention, the functions of the various substances are as follows:
[0024] As a part of thermal insulation film, nano indium tin oxide powder has good optical properties and thermal insulation effect.
[0025] Nano-tungsten oxide powder increases the wear resistance and scratch resistance of the film, while improving the thermal insulation performance.
[0026] Nano-titanium oxide improves the weather resistance and UV resistance of the film.
[0027] Nano zinc oxide powder has antibacterial and anti-ultraviolet functions, enhancing the protective performance of the thermal insulation film.
[0028] Sodium citrate acts as a grinding aid to help nanopowders mix and grind better.
[0029] Isopropyl tri(dioctyl pyrophosphate) titanate is used as a coupling agent to improve the compatibility and bonding force between the inorganic nanopowder and the organic polymer.
[0030] The modified materials improve the overall performance of the thermal insulation film, such as tensile strength, heat resistance and optical properties, through specific chemical reactions and polymerization processes.
[0031] Polyethylene terephthalate, as the base material of the thermal insulation film, provides good optical transparency and mechanical properties.
[0032] Polyisobutylene acts as a plasticizer to improve the flexibility and processing properties of the film.
[0033] Polyvinylpyrrolidone acts as a dispersant, helping other ingredients to be evenly dispersed in the solution.
[0034] Ethylene-vinyl acetate copolymer improves the flexibility and adhesive properties of the film.
[0035] The UV absorber absorbs UV rays and protects the thermal insulation film from being damaged by UV rays.
[0036] Light stabilizer 770 improves the light resistance of the film and prevents light aging.
[0037] BYK-310 leveling agent improves the surface quality of the coating, making it smoother and flatter.
[0038] Silicone defoamers reduce bubbles generated during the coating process and improve film clarity.
[0039] Dibenzoyl peroxide acts as a free radical initiator to initiate the polymerization reaction.
[0040] 1,1,2,2-Tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane provides fluorine atoms, increasing the chemical stability and weather resistance of the material.
[0041] (2Z)-3-(Cyclopropylcarbamoyl)prop-2-enoic acid provides carbamoyl groups, which enhance the crosslinking density and mechanical strength of the material.
[0042] Polyurethane resin serves as the matrix of the modified material, providing excellent mechanical properties and chemical resistance.
[0043] Hexamethylene diisocyanate is used as a cross-linking agent to improve the cross-linking density and three-dimensional network structure of the material, thereby enhancing its heat resistance and mechanical properties.
[0044] Compared with the prior art, it has the following beneficial effects:
[0045] 1) The present invention effectively improves the infrared and ultraviolet blocking rate of the automotive thermal insulation film by introducing specific nano-oxides and modified materials, and enhances the film's ability to reflect and absorb solar heat, thereby more effectively blocking external heat from entering the vehicle and improving the thermal insulation efficiency.
[0046] 2) The present invention combines nano-oxides with modified materials and adopts a specific preparation method to make the final thermal insulation film have higher tensile strength. This enhanced mechanical property helps to improve the durability and impact resistance of the film, extend its service life, and ensure that its functionality and integrity are maintained under various usage conditions.
[0047] 3) The thermal insulation film preparation method of the present invention adopts more environmentally friendly materials and processes, which not only reduces the impact on the environment, but also helps to reduce the energy consumption of the air conditioner in the car due to the improved thermal insulation performance, thereby saving energy and reducing carbon emissions; in addition, by controlling the ultraviolet blocking rate of the film, the present invention also helps to protect the passengers in the car from the harm of ultraviolet rays, while protecting the interior decoration of the car from fading or aging caused by ultraviolet rays. DETAILED DESCRIPTION
[0048] Main sources of substances:
[0049] Nano-indium tin oxide powder: average particle size: 30nm, purity: 99.9%, specific surface area: 35m 2 / g, crystal shape: spherical, color: light blue.
[0050] Nano tungsten oxide powder: content ≥99.9%, particle size: 50nm, appearance: blue.
[0051] Nano titanium oxide: average particle size: 100nm, purity: 99.9%, crystal form: rutile, color: white.
[0052] Nano zinc oxide powder: particle size: 30-50nm, appearance: white powder, content: 99.7%.
[0053] Isopropyl tri(dioctyl pyrophosphate) titanate: CAS: 67691-13-8, chemical formula: C 51 H 112 O 22 P6Ti, molecular weight: 1311.13.
[0054] Polyethylene terephthalate: Brand: DuPont, USA, specification model: 545NC010.
[0055] Polyisobutylene: Brand: Dalin, Korea, molecular weight: 950, viscosity 100C (cst): 230±10, pour point ℃: -9±5, flash point ℃: 190.
[0056] Polyvinylpyrrolidone: Item No.: PVP K30, Jinhai Iodine (Shandong) New Material Technology Co., Ltd.
[0057] Ethylene-vinyl acetate copolymer: Manufacturer (Origin): Hanwha, South Korea, Product Name: EVA.
[0058] Ultraviolet absorber: single product number: uv-531, Dongguan Dinghai Plastic Chemical Co., Ltd.
[0059] Light stabilizer 770: CAS: 52829-07-9, Brand: Senfida.
[0060] BYK-310 leveling agent: Brand: BYK.
[0061] Silicone defoamer: Product number: CI-0560, Guangdong Nanhui New Materials Co., Ltd.
[0062] Polyurethane resin: Model: Neorez R3986, content ≥35(%), density: 1.4(g / cm 3 ), Shanghai Youci New Materials Co., Ltd.
[0063] 1,1,2,2-Tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane: CAS No.: 1998-53-4 Molecular formula: C6F 10 O2.
[0064] (2Z)-3-(Cyclopropylcarbamoyl)prop-2-enoic acid: CAS number: 27995-78-4, molecular formula: C7H9NO3.
[0065] Perfluoro-3-oxabutyl vinyl ether: CAS No.: 39499-31-5 Molecular formula: C5F 10 O2.
[0066] Perfluoroethyl vinyl ether: CAS number: 10493-43-3 Molecular formula: C4F8O.
[0067] Tetrafluoroethylene: CAS number: 116-14-3 Molecular formula: C2F4.
[0068] 2-Methyl-N-[3-(trimethoxysilyl)propyl]-2-acrylamide: CAS No.: 10310-41-5 Molecular formula: C 10 H 21 NO4Si.
[0069] Triethoxysilylpropylmaleic acid: CAS No.: 33525-68-7 Molecular formula: C 13 H 25 NO6Si.
[0070] Vinyltriethoxysilane: CAS No.: 78-08-0 Molecular formula: C8H 18 O3Si.
[0071] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0072] The design idea of the present invention is to prepare a car thermal insulation film with excellent thermal insulation performance and mechanical strength. By combining nano oxide powder with a specific modified material, ultrasonic vibration technology is used to achieve uniform dispersion of the powder, and then mixed with polymers such as polyethylene terephthalate and polyisobutylene to form a high-performance composite slurry. In this process, 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid are specially selected as key components of the modified material to enhance the tensile strength of the film and the infrared and ultraviolet light blocking rate. This modified material not only improves the optical properties and weather resistance of the thermal insulation film, but also enhances its absorption and reflection ability of ultraviolet rays by introducing fluorine atoms, thereby achieving effective control of the temperature inside the car, improving riding comfort and reducing energy consumption. In addition, the preparation method also takes environmental protection factors into consideration, avoids the use of substances harmful to the environment, and meets the current demand for green materials.
[0073] Example 1
[0074] A method for preparing an automobile thermal insulation film is as follows:
[0075] Step 1, take 0.5kg of nano indium tin oxide powder, 0.1kg of nano tungsten oxide powder, 0.1kg of nano titanium oxide, 0.1kg of nano zinc oxide powder and 0.1kg of sodium citrate, put them into a ball mill for mixing and grinding; mix the obtained mixed powder with 5kg of water, and perform ultrasonic oscillation for 50 minutes to achieve dispersion, the ultrasonic power is 300W, and the ultrasonic frequency is 40kHz, add 0.03kg of isopropyl tri (dioctyl pyrophosphate acyloxy) titanate and 1.2kg of modified material to the dispersion, and stir well to form a uniform composite slurry;
[0076] Step 2, weighing 1.6 kg of polyethylene terephthalate and 0.2 kg of polyisobutylene, dissolving them in 20 kg of ethyl acetate, adding 0.1 kg of polyvinyl pyrrolidone, stirring to make it uniformly dispersed, adding 20 kg of water to the mixture, continuing to stir, and removing ethyl acetate through a distillation process, adding 0.012 kg of ethylene-vinyl acetate copolymer, 0.01 kg of ultraviolet absorber, 0.002 kg of light stabilizer 770, 0.005 kg of BYK-310 leveling agent, 0.001 kg of silicone defoamer, mixing until a uniform state, to obtain a mixture; adding the composite slurry obtained in step 1 to the above mixture, stirring thoroughly, and evaporating the water so that the solid content reaches 75%, thereby preparing a mixed slurry for coating;
[0077] Step 3: evenly apply the mixed slurry obtained in step 2 on the glass surface, and the wet film thickness of the coating is controlled at 0.18 mm. The coated glass is placed in an oven for drying until the solvent in the slurry is completely volatilized to obtain a car thermal insulation film.
[0078] The preparation method of the modified material is as follows:
[0079] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0080] S2, weigh 8 kg of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 9 kg of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, add them to 30 kg of ethyl acetate, heat to 70° C. and keep for 15 minutes, dropwise add the initiator solution of step S1, raise the temperature to 100° C., keep for 1.5 hours, and obtain a pretreated product;
[0081] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0082] Example 2
[0083] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0084] The preparation method of the modified material is as follows:
[0085] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0086] S2, weighing 8 kg of perfluoro-3-oxabutyl vinyl ether and 9 kg of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, adding them to 30 kg of ethyl acetate, heating to 70 ° C and maintaining for 15 minutes, adding the initiator solution of step S1 dropwise, heating to 100 ° C, maintaining for 1.5 hours, and obtaining a pretreated product;
[0087] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0088] Example 3
[0089] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0090] The preparation method of the modified material is as follows:
[0091] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0092] S2, weighing 8 kg of perfluoroethyl vinyl ether and 9 kg of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, adding them to 30 kg of ethyl acetate, heating to 70 ° C and maintaining for 15 minutes, adding the initiator solution of step S1 dropwise, heating to 100 ° C, maintaining for 1.5 hours, and obtaining a pretreated product;
[0093] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0094] Example 4
[0095] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0096] The preparation method of the modified material is as follows:
[0097] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0098] S2, weigh 8 kg of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 9 kg of 2-methyl-N-[3-(trimethoxysilyl)propyl]-2-acrylamide, add them to 30 kg of ethyl acetate, heat to 70° C. and keep for 15 minutes, add the initiator solution of step S1 dropwise, heat to 100° C., keep for 1.5 hours, and obtain a pretreated product;
[0099] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0100] Example 5
[0101] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0102] The preparation method of the modified material is as follows:
[0103] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0104] S2, weigh 8 kg of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 9 kg of vinyltriethoxysilane, add them to 30 kg of ethyl acetate, heat to 70° C. and keep for 15 minutes, add the initiator solution of step S1 dropwise, heat to 100° C., keep for 1.5 hours, and obtain a pretreated product;
[0105] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0106] Comparative Example 1
[0107] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0108] The preparation method of the modified material is as follows:
[0109] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0110] S2, weighing 8 kg of tetrafluoroethylene and 9 kg of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, adding them to 30 kg of ethyl acetate, heating to 70 ° C and maintaining for 15 minutes, adding the initiator solution of step S1 dropwise, heating to 100 ° C, maintaining for 1.5 hours, and obtaining a pretreated product;
[0111] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0112] Comparative Example 2
[0113] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0114] The preparation method of the modified material is as follows:
[0115] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0116] S2, weigh 8 kg of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 9 kg of triethoxysilylpropylmaleic acid, add them to 30 kg of ethyl acetate, heat to 70° C. and keep for 15 minutes, add the initiator solution of step S1 dropwise, heat to 100° C., keep for 1.5 hours, and obtain a pretreated product;
[0117] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0118] Comparative Example 3
[0119] The preparation method of a car thermal insulation film is basically the same as that of Example 1, the only difference being that the preparation method of the modified material is different.
[0120] The preparation method of the modified material is as follows:
[0121] S1, weigh 0.02 kg of dibenzoyl peroxide, mix it with 5 kg of ethyl acetate, and stir until uniform to obtain an initiator solution;
[0122] S2, weigh 8 kg of tetrafluoroethylene and 9 kg of triethoxysilylpropyl maleic acid, add them to 30 kg of ethyl acetate, heat to 70 ° C and keep for 15 minutes, dropwise add the initiator solution of step S1, heat to 100 ° C, keep for 1.5 hours, and obtain a pretreated product;
[0123] S3. Mix the pretreated material obtained in step S2, 40 kg of polyurethane resin, and 0.08 kg of hexamethylene diisocyanate, heat to 60° C., and maintain for 50 minutes to obtain a modified material.
[0124] Comparative Example 4
[0125] A method for preparing an automobile thermal insulation film is as follows:
[0126] Step 1, take 0.5kg of nano indium tin oxide powder, 0.1kg of nano tungsten oxide powder, 0.1kg of nano titanium oxide, 0.1kg of nano zinc oxide powder and 0.1kg of sodium citrate, put them into a ball mill for mixing and grinding; mix the obtained mixed powder with 5kg of water, and perform ultrasonic vibration for 50 minutes to achieve dispersion, the ultrasonic power is 300W, and the ultrasonic frequency is 40kHz, add 0.03kg of isopropyl tri (dioctyl pyrophosphate acyloxy) titanate and 1.2kg of polyurethane resin to the dispersion, and stir thoroughly to form a uniform composite slurry;
[0127] Step 2, weighing 1.6 kg of polyethylene terephthalate and 0.2 kg of polyisobutylene, dissolving them in 20 kg of ethyl acetate, adding 0.1 kg of polyvinyl pyrrolidone, stirring to make it uniformly dispersed, adding 20 kg of water to the mixture, continuing to stir, and removing ethyl acetate through a distillation process, adding 0.012 kg of ethylene-vinyl acetate copolymer, 0.01 kg of ultraviolet absorber, 0.002 kg of light stabilizer 770, 0.005 kg of BYK-310 leveling agent, 0.001 kg of silicone defoamer, mixing until a uniform state, to obtain a mixture; adding the composite slurry obtained in step 1 to the above mixture, stirring thoroughly, and evaporating the water so that the solid content reaches 75%, thereby preparing a mixed slurry for coating;
[0128] Step 3: evenly apply the mixed slurry obtained in step 2 on the glass surface, and the wet film thickness of the coating is controlled at 0.18 mm. The coated glass is placed in an oven for drying until the solvent in the slurry is completely volatilized to obtain a car thermal insulation film.
[0129] Test Example 1
[0130] The tensile strength is measured with reference to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets";
[0131] The test results are shown in Table 1.
[0132] Table 1
[0133] Experimental protocol Tensile strength(MPa) Example 1 48.4 Example 2 45.6 Example 3 44.1 Example 4 44.8 Example 5 45.6 Comparative Example 1 42.7 Comparative Example 2 44.5 Comparative Example 3 41.7 Comparative Example 4 37.9
[0134] Test Example 2
[0135] According to the QC / T 1170-2022 "Functional Film for Automobile Glass" standard, the thermal insulation film performance test of the present invention includes the following two parts:
[0136] 1. Evaluation of infrared blocking performance: This test uses a Hitachi U-4100 spectrometer to measure the transmittance of the thermal insulation film samples of Examples 1 to 5 of the present invention and Comparative Examples 1 to 4 in the near-infrared region of the solar spectrum, i.e., wavelengths of 1400nm to 2500nm. Based on the transmittance data obtained, the infrared blocking rate of each sample is calculated.
[0137] 2. Evaluation of UV blocking performance: This test also uses the Hitachi U-4100 spectrometer to measure the transmittance of the above samples in the ultraviolet region of the solar spectrum, that is, wavelengths from 300nm to 380nm. Based on the measurement results, the UV blocking rate of each sample is calculated.
[0138] The test results are shown in Table 2.
[0139] Table 2
[0140] Experimental protocol Infrared blocking rate (%) UV blocking rate (%) Example 1 93.6 98.4 Example 2 91.5 96.1 Example 3 91.0 95.4 Example 4 90.6 95.2 Example 5 90.2 94.3 Comparative Example 1 89.1 93.0 Comparative Example 2 89.9 94.7 Comparative Example 3 87.3 92.5 Comparative Example 4 82.6 89.7
[0141] It can be seen from the data in Tables 1 and 2 that the automotive thermal insulation film prepared in Example 1 has the best test results for tensile strength, infrared blocking rate and ultraviolet blocking rate.
[0142] In Example 1 of the present invention, the 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane used has a symmetrical structure, which makes the interaction force between its molecules stronger, thereby improving the physical properties of the polymer. The two double bonds in the compound provide additional reactive sites, which help to form a more stable cross-linked network during the polymerization process. This highly ordered and tight molecular structure not only enhances the tensile strength of the material, but also improves the infrared and ultraviolet light blocking efficiency. Due to the high electronegativity of fluorine atoms, this structure also helps to improve the optical transparency and chemical resistance of the material, which is crucial to the performance of automotive thermal insulation films. Therefore, compared with other embodiments and comparative examples, the material in Example 1 exhibits better comprehensive performance, including higher tensile strength and better infrared and ultraviolet blocking rates.
[0143] The (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid used in Example 1 has a specific molecular structure, including a cyclopropylcarbamoyl group and an acrylic acid double bond, and this structure provides excellent reactivity and cross-linking ability. The presence of the cyclopropyl group increases the rigidity and stability of the molecule. In addition, the presence of the acrylic acid double bond allows the molecule to be copolymerized with other monomers, further enhancing the cross-linking density and network structure of the polymer. The combination of this structure not only improves the tensile strength of the modified material, but also enhances its infrared and ultraviolet light blocking ability. Therefore, compared with other monomers used in Examples 4 and 5, and compared with the triethoxysilylpropyl maleic acid in Comparative Example 2, the (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid in Example 1 provides better comprehensive performance, thereby obtaining an automotive thermal insulation film with higher tensile strength, infrared blocking rate and ultraviolet blocking rate.
[0144] In Example 1, the modified material achieves excellent tensile strength, infrared blocking rate and ultraviolet blocking rate by combining 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid. The fluorine atoms in 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane provide strong electron attraction ability, enhance the van der Waals force between molecules, thereby improving the cohesion and tensile strength of the material. At the same time, the high electronegativity of fluorine atoms helps to block ultraviolet and infrared rays because fluorine atoms can absorb light energy in these spectral regions. On the other hand, the introduction of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid not only increases the rigidity of the molecule, but its cyclopropyl structure can also improve the heat resistance and chemical resistance of the material, while the carbamoyl group enhances the hydrogen bonding between molecules, further improving the mechanical properties of the material. The synergistic effect of these two components enables the modified material to effectively block ultraviolet and infrared rays while maintaining high transparency, thus surpassing the performance of directly used polyurethane resins and making it more suitable for the application of high-performance automotive thermal insulation films.
Claims
1. A method for preparing an automobile thermal insulation film, characterized in that: The method is as follows, in parts by weight: Step 1, taking 0.4-0.6 parts of nano indium tin oxide powder, 0.05-0.2 parts of nano tungsten oxide powder, 0.05-0.2 parts of nano titanium oxide, 0.05-0.2 parts of nano zinc oxide powder and 0.05-0.2 parts of grinding aid, putting them into a ball mill for mixing and grinding; mixing the obtained mixed powder with 4-6 parts of water, and performing ultrasonic vibration to achieve dispersion, adding 0.02-0.04 parts of coupling agent and 1-1.5 parts of modified material to the dispersion, and stirring them thoroughly to form a uniform composite slurry; Step 2, weighing 1.4-1.8 parts of polyethylene terephthalate and 0.1-0.3 parts of plasticizer, dissolving them in 15-25 parts of ethyl acetate, adding 0.05-0.2 parts of dispersant, stirring to make it uniformly dispersed, adding 15-25 parts of water to the mixture, continuing to stir, and removing ethyl acetate through a distillation process, adding 0.01-0.015 parts of ethylene-vinyl acetate copolymer, 0.005-0.02 parts of ultraviolet absorber, 0.001-0.003 parts of light stabilizer 770, 0.004-0.06 parts of BYK-310 leveling agent, 0.0005-0.002 parts of silicone defoamer, mixing until a uniform state, to obtain a mixture; adding the composite slurry obtained in step 1 to the above mixture, stirring fully, and evaporating water to prepare a mixed slurry for coating; Step 3: evenly apply the mixed slurry obtained in step 2 on the glass surface to obtain a coating, and place the coated glass in an oven for drying until the solvent in the slurry is completely volatilized to obtain a car thermal insulation film.
2. The method for preparing the automotive thermal insulation film according to claim 1, characterized in that: The grinding aid is sodium citrate.
3. The method for preparing the automotive thermal insulation film according to claim 1, wherein the ultrasonic oscillation time is 40 to 60 minutes, the ultrasonic power is 200 to 400 W, and the ultrasonic frequency is 20 to 60 kHz.
4. The method for preparing an automotive thermal insulation film according to claim 1, wherein the coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.
5. The method for preparing the automotive thermal insulation film according to claim 1, wherein the plasticizer is polyisobutylene. 6 . The method for preparing the automotive thermal insulation film according to claim 1 , wherein the dispersant is polyvinyl pyrrolidone.
7. The method for preparing the automotive thermal insulation film according to claim 1, wherein the evaporated water is such that the solid content reaches 70-80%.
8. The method for preparing an automotive thermal insulation film according to claim 1, wherein the wet film thickness of the coating is controlled to be 0.15 to 0.25 mm.
9. The method for preparing the automotive thermal insulation film according to claim 1, wherein the preparation method of the modified material is as follows, in parts by weight: S1. Weigh 0.01-0.03 parts of dibenzoyl peroxide, mix it with 4-6 parts of ethyl acetate, and stir until uniform to obtain an initiator solution; S2, weigh 5 to 10 parts of 1,1,2,2-tetrafluoro-1,2-bis[(trifluorovinyl)oxy]ethane and 8 to 10 parts of (2Z)-3-(cyclopropylcarbamoyl)prop-2-enoic acid, add them to 25 to 35 parts of ethyl acetate, heat to 60 to 80° C. and keep for 10 to 20 minutes, dropwise add the initiator solution of step S1, heat to 90 to 110° C., keep for 1 to 2 hours, and obtain a pretreated product; S3, mixing the pretreated material obtained in step S2, 30 to 50 parts of polyurethane resin, and 0.05 to 0.1 parts of hexamethylene diisocyanate, heating to 50 to 70° C., and maintaining for 40 to 60 minutes to obtain a modified material.
10. A car thermal insulation film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-transparency ultraviolet-blocking energy-saving film and solution-fusion preparation method thereof
CN101967299A
Transparent colored heat and ultraviolet insulation film and preparation method thereof
CN103435983A
Polymer containing a carbamoyl group and preparation method thereof
CN104844759A
Heat insulating coating film for front windshield of automobile and preparation method of heat insulating coating film
CN106833242A
Cited By
Transparent film with anti-electromagnetic radiation and anti-blue light performance and preparation method thereof
CN120505006A
Transparent film with electromagnetic radiation and blue light resistance and preparation method thereof
CN120505006B
Transparent film for blocking infrared rays and ultraviolet rays and preparation method thereof
CN121270998A